LEXICON ICONOGRAPHICUM MYTHOLOGIAE CLASSICAE. VI: KENTAURIDES - OIAX. 2 vols. In: VI, encadernado. vol. I, texto, V-XXX - 1-91 p., vol. 2 pranchas, 772 p. com 718 figuras. Zürich-München: Artemis Verlag, 1992. - Fellone, Roseli (Classica - Revista Brasileira de Estudos Clássicos, 1995)
.